2011
DOI: 10.1002/med.20239
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming tumor multidrug resistance using drugs able to evade P‐glycoprotein or to exploit its expression

Abstract: Multidrug resistance (MDR) is a major obstacle to the effective treatment of cancer. Cellular overproduction of P-glycoprotein (P-gp), which acts as an efflux pump for various anticancer drugs (e.g. anthracyclines, Vinca alkaloids, taxanes, epipodophyllotoxins, and some of the newer antitumor drugs) is one of the more relevant mechanisms underlying MDR. P-gp belongs to the superfamily of ATP-binding cassette transporters and is encoded by the ABCB1 gene. Its overexpression in cancer cells has become a therapeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
90
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(91 citation statements)
references
References 269 publications
(478 reference statements)
0
90
0
1
Order By: Relevance
“…A previous study (33) have shown that the brain distribution of several quinolones, including levofloxacin, is limited due to the action of multiple efflux transporters, including MRP family drug efflux pumps and P-glycoprotein (Pgp). Comparatively, cellular overproduction of P-gp has been described as one of the major causes for multidrug resistance in prostate tumor cells, since P-gp acts as an efflux pump for various anticancer drugs with a wide variety of chemical structures, being an obstacle to the effective treatment of prostate cancer (34). However, the role of P-gp and other transporters on quinolone distribution in the prostate has not yet been a focus of investigation.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study (33) have shown that the brain distribution of several quinolones, including levofloxacin, is limited due to the action of multiple efflux transporters, including MRP family drug efflux pumps and P-glycoprotein (Pgp). Comparatively, cellular overproduction of P-gp has been described as one of the major causes for multidrug resistance in prostate tumor cells, since P-gp acts as an efflux pump for various anticancer drugs with a wide variety of chemical structures, being an obstacle to the effective treatment of prostate cancer (34). However, the role of P-gp and other transporters on quinolone distribution in the prostate has not yet been a focus of investigation.…”
Section: Discussionmentioning
confidence: 99%
“…P-glycoprotein overexpressed in multidrug-resistant cancer cells could induce the chemotherapy drugs to pump from the cells. 4,5 Unfortunately, no P-glycoprotein inhibitors have been approved for clinical use after the failure of valspodar (PSC-833). 19 On the other hand, apoptosis is an important metabolic step in regulating cell numbers and their growth, and multiple antiapoptotic signals have been shown to enable cancer cells to evade destruction by chemotherapeutic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…4 Chinese herbal medicine, nanoparticles, and hyperthermia have contributed a lot to this line of research. [5][6][7] It is well known that hyperthermia adjuvant to chemotherapy is playing an increasing role in the treatment of multidrug-resistant tumors in vivo, but temperature has been difficult to control.…”
Section: Introductionmentioning
confidence: 99%
“…The multidrug resistant phenotype, and in particular the overexpression of ABCB1, also confers cross-resistance to sev- [22][23][24].…”
Section: Vinca Alkaloids (Vinorelbine Vinblastine)mentioning
confidence: 99%